Theories and Concepts of Islamic Education - Brayen Jodi Forester; Ahmad Zainuri (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Islamic education is an educational system oriented toward the holistic development of human beings through the integration of spiritual, intellectual, moral, and social values. This article aims to comprehensively examine the theories and concepts of Islamic education by analyzing its definitions, objectives, and scope based on classical sources, contemporary scholarly perspectives, and findings from previous studies. This study employs a library research approach by examining the Qur’an, Hadith, classical scholarly works, academic books, and relevant national and international journal articles. The findings indicate that Islamic education functions not merely as a process of transmitting religious knowledge, but also as a medium for moral formation, intellectual development, and the strengthening of learners’ social responsibility. The concepts of tarbiyah, ta‘lim, and ta’dib serve as the foundational framework in constructing a holistic and adaptive model of Islamic education. Furthermore, this study highlights that Islamic education remains highly relevant in responding to modern challenges such as globalization and digital transformation, provided that it consistently upholds its normative Islamic values. Therefore, Islamic education needs to be developed through an integrative and contextual approach in order to produce generations who are faithful, knowledgeable, morally upright, and capable of actively participating in contemporary society.